Back Cover: A layered antiferromagnetic semiconductor EuMTe3 (M = Bi, Sb) (Phys. Status Solidi RRL 12/2015). Issue 12 (December 2015) - Niu, Ying Y.; Wu, Dong; Shen, Liang; Wang, Biao
Abstract : No abstract is available for this article. Abstract : With the hexagonal structure suggested for LnMTe3 (Ln = lanthanides, M = Bi, Sb), few experiments were able to support the existence of these materials. Furthermore, high‐temperature metallurgy and flux methods have been reported unsuccessfully utilized in the synthesis of them. In the Letter on pp. 735–739, Ying Y. Niu et al. report the synthesis and characterization of novel EuMTe3 (M = Bi, Sb) compounds. These compounds are synthesized by the flux method under a mild temperature of ∼700 °C and crystallized in the Pmmn space group with layered structure consisting of Te sheets and M/Eu/Te slabs. From the resistivity and optical measurements, EuMTe3 are semiconductors with energy gap of 0.1–0.3 eV. Both EuMTe3 compounds have a long‐range AFM ordering below about 8 K, revealing that these compounds are antiferromagnetic semiconductors. At low temperature and magnetic field, an abnormal positive magnetoresistance (MR) followed by a large negative MR at higher magnetic fields was detected, rendering a strong spin–orbit coupling with a possible novel quantum‐interference between localization and weak anti‐localization effects suggested in the present system.